United Nations Efforts to Combat and Reduce Violence Against Women - Nayyef, Hussein; Mhmood, Luma (Journal of Legal Sciences, 2023)
The phenomenon of violence against women is one of the phenomena that has attracted wide global attention, and due to the aggravation of this phenomenon, its exacerbation and its threat to women’s rights as human beings and its destruction of the principle of gender equality, this phenomenon has found its resonance at the level of the United Nations Organization to take the status of a crime and a violation of human rights that the United Nations works to protect Therefore, the General Assembly, in addition to other bodies, made various efforts to combat violence against women as a phenomenon that hinders the achievement of security, stability and development. Its efforts were embodied in concluding international agreements and issuing relevant international declarations as well as holding international conferences in addition to issuing a number of international resolutions.